Strengthening Religious Moderation from an Early Age through the Children's Moral Education Program in the Tpq Ar-Roudhoh Bumi Ayu Bengkulu Environment - Efril Rivan; Elma Septiyana; Elda Konita; Merda Gustiana; Cut Della Ayu Andhini; Sanja Faherira; Viona Femelia; Marsanda Antika Putri; Qori'atun Hasanah; Intan Utami (Edumaspul: Jurnal Pendidikan, 2026)
The formation of moderate character from an early age in the Taman Pendidikan Al-Qur'an (TPQ) environment is a strategic preventive measure in shielding the younger generation from the potential of religious exclusivism. This Thematic Community Service (KKN) activity by Group 17 aims to strengthen the values of religious moderation through the restructuring of the children's moral education program at TPQ Ar-Roudhoh based at the Baitul Izzah Mosque, Jalan Intan, RT 01, Bumi Ayu Village, Bengkulu City. The implementation method uses the Asset-Based Community Development (ABCD) approach which focuses on utilizing the internal potential of the local community. The results of the activity showed a significant increase in students' conceptual and practical understanding of moderation pillars (tolerance, compassion, and togetherness) as well as strengthening the teaching capacity of educators through interactive moral modules. Impact evaluation using the Societal Impact Index (SII) confirmed the program's satisfaction and effectiveness level at 93.4% (very high category). The resulting social impacts include the formation of an inclusive non-formal education ecosystem, increased active participation of student guardians, and the strengthening of socio-religious cohesion in the Bumi Ayu Village, Bengkulu